The unlikely ‘antiquity of Madagascar's grasslands’: Disproportionately forest‐limited endemic fauna support anthropogenic transformation from woodland - Grant S. Joseph; Colleen L. Seymour (Journal of Biogeography, 2021)
Papers arguing for Malagasy central highlands (MCH) as natural grassland rely disproportionally on a single reference (Bond et al. 2008, The antiquity of Madagascar's grasslands and the rise of C4 grassy biomes. Journal of Biogeography , 35 , 1743–1758). The paper argues that (1) evolution of endemic grassland specialist fauna, (2) paleoecological findings and (3) existence of subfossil C 4 ‐grazers provide evidence that when humans entered the MCH around 2000 years before present (BP), it was a natural, ancient grassland. Respectfully, we find discrepancies between that study and its sources: (1) proportions of endemic grassland‐limited species are 17‐fold greater than original data (which show 87% of species are forest‐limited and 2% [not 32%] are grassland‐limited); (2) paleodata relevant to human‐influenced timeframes are omitted; and (3) the hippo specimen used to invoke existence of ancient C 4 ‐grazers was the common hippo from mainland Africa, circa 1950. We conclude that the paper's findings are unsupported, and MCH grasslands are likely anthropogenic.